ANALYSIS OF LIQUIDITY AND SOLVENCY RATIOS ON THE BALANCE SHEET OF THE REGIONAL GOVERNMENT OF TEMANGGUNG IN 2014-2015 - Edo Rudianto (Transpublika Publisher, 2022)
The purpose of this study is to determine the ratio of liquidity and solvency on the balance sheet of the Temanggung Regional Government. The object of research used is the balance sheet of the Temanggung Regional Government for the period of 2014-2015. The method used is descriptive qualitative method. The results of this study indicate that the Temanggung district government has sufficient assets to pay off its debts and can pay debts quickly and with a high level of liquidity. Hence, it can be concluded that the Temanggung district government has financial adequacy to carry out government operational activities, and able to fulfill all its obligations, both short-term and long-term obligations, as well as the Temanggung district government has the opportunity to attract investors and creditors to channel their funds for the development of the Temanggung government.